Penser la physique du pouvoir. La possession de la juridiction dans les commentaires d’Innocent IV et d’Antonio de Budrio à la décrétale Dilectus - Marta Madero (Clio@Themis, 2016)
Dated 1201, the Dilectus decretal of Innocent III is included into the 3 Compilatio (3.29.c.un.) and the Liber Extra (3.37.2). Since Innocent IV’s comment (ca. 1245), it became a reference value for the theme of possession of jurisdiction. His reading has been systematically taken over by decretalists. The text of Antonio Budrio constitutes an original contribution, and can be divided into two axes. The first one is about jurisdiction, the thing we have, upon which power exists. The second is about the force that grasps, the way to express judicially his action.